The prophet of Harvard Law : James Bradley Thayer and his legal legacy - Porwancher, Andrew; Mazeitis, Jake; Jipp, Taylor; Coffey, Austin (American political thought., 2022)
"A legendary professor at Harvard Law from 1874 to 1902, James Bradley Thayer shaped generations of students who would become Supreme Court justices, leading appellate judges, and elite law school deans. The most iconic names of the Progressive Era legal world-Oliver Wendell Holmes, Jr., Louis Brandeis, Learned Hand, Roscoe Pound, John Henry Wigmore-all came under his tutelage. Thayer imparted to them a set of jurisprudential values, befitting a modernizing society, that would come to be known as "legal realism." At a time when Harvard Law became the forerunner of modern professional education, he counted among its small but nimble faculty who pioneered innovations for thirty years. Thayer drew from these experiences to advance a jurisprudence that met the moment. This book, for the first time, tells the story of James Bradley Thayer and documents his astounding influence on American law. The opening chapters examine Thayer's life and work, while the rest of the study explores his legacy and influence on the Thayerites-Holmes, Brandeis, Wigmore, Hand, Pound, and Felix Frankfurter"--